Over view on Data Mining in Social Media - Amali Pushpam, C; Gnana Jayanthi, J (International Journal of Computer Sciences and Engineering, 2025)
Knowledge plays a vital role in every sphere of human life. Data Mining supports to acquire knowledge by discovering pattern / correlations among data. This information is applied in various applications like business, education, social media, medical, Agriculture etc. Data mining field has attained enormous success from its inception to the present level. Also it faces many issues especially while handling social media data. Social media is one of the important sources that provide huge volume of data that are unstructured and heterogeneous. Handling this data is really a very big challenge to the researchers. At present, a number of data mining algorithms and techniques are available with their own merits and demerits. Finding a suitable algorithm for a particular application is a very big challenge. This paper imparts many issues in data mining and also focuses scope of the data mining in social media which will be helpful in the further research.